ANALISIS WAKTU DAN BIAYA BERDASARKAN ANALISA PRODUKTIVITAS TENAGA KERJA PADA PEMBANGUNAN PUSKESMAS MENINTING KABUPATEN LOMBOK BARAT - I GEDE PUTU WARKA; ZAEDAR GAZALBA; TETI HANDAYANI (GANEC SWARA, 2023)
The contruction of Meninting Puskesmas is a government development in 2019 that CV. Langko Express working on. On the development of this project, a schedule of time of employment planning is made based on liberal experience obtained and is not calculated analytically or by Indonesia's national standards (SNI). So at the time of execution in the field, the cost of the job, the time of realization and productivity of the labor in the field is different from planned.This research carried out in three stages, the first was determining research location, then the second stage was collecting and preparing data, and last stage was analyzing data. When analyzing work costs, implementation time and labor productivity, researchers use the standards set by the government, namely SNI. Regulation of the Minister of Public Works for Public Housing Number: 28 / PRT / M / 2016 concerning Analysis of Unit Prices for Public Works.According to data analysis result that has been carried out, it can be seen that the amount of time obtained based on the 2016 SNI Index is 385 days total cumulative time for each work item, but with an S curve graph it takes 67 days with a total workforce of 526 people and with total budget plan for work costs of  Rp. 187,514,556.00 while according to data in the field with the same number of workers the time required is 286 days and with the S curve graph it takes 50 days at a cost of Rp. 117,102,000.00. Therefore, it can be said that realization in the field is 99 days faster and can save labor wages by Rp. 70,412,556.00. The construction of Meninting Health Center has a workforce productivity of 160% and has a profit percentage of 38% greater than the 2016 SNI analysis